Fuel cell type H2 gas sensor structure, membrane electrode and preparation method thereof

By using modified SnO2 as a carrier to prepare Pt/SnO2 or Pt/SnO2-Pd sensitive electrodes, the problem of low detection sensitivity of existing hydrogen sensors is solved, and a significant reduction in the hydrogen detection limit and long-term stability of the sensor is achieved.

CN115452914BActive Publication Date: 2025-03-18HUAZHONG UNIV OF SCI & TECH

Patent Information

Application Number
CN202210966479.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-12
Publication Date
2025-03-18
Estimated Expiration
2042-08-12

AI Technical Summary

Technical Problem

Existing hydrogen gas sensors have problems with high power consumption, poor selectivity and low detection sensitivity, especially the sensitive electrode composed of traditional carbon material support and Pt-based modification catalysts reduces active sites, reduces response values, and short lifespans.

Method used

SnO2 is used as a carrier and Pt nanoparticles are modified to obtain Pt/SnO2 or Pt/SnO2-Pd as the sensitive electrode material. By controlling the mass ratio of Pt:SnO2 and the mass ratio of Pd, membrane electrodes are prepared to improve the sensitivity of hydrogen detection.

Benefits of technology

The detection limit of hydrogen by fuel cell type H2 gas sensor is as low as 1 ppm, which is far lower than the detection limit of existing electrochemical sensors, and the long-term stability and detection sensitivity of the sensor are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115452914B_ABST
    Figure CN115452914B_ABST
Patent Text Reader

Abstract

The invention discloses a membrane electrode for a fuel cell type H2 gas sensor and a preparation method thereof. The preparation method comprises: adding SnO2 powder or SnO2-Pd powder to a chloroplatinic acid solution and adding sodium citrate and stirring to obtain a substance A; adding a sodium borohydride alkaline solution to the substance A under ice-water bath conditions, heating in a water bath at 60-90°C for 1-2h to obtain a substance B; centrifuging and washing the substance B, and drying to obtain a target powder, wherein the target powder is Pt / SnO2 powder or Pt / SnO2-Pd powder, wherein Pt / SnO2 is SnO2 modified by Pt nanoparticles, and Pt / SnO2-Pd is SnO2-Pd modified by Pt nanoparticles, and the mass ratio of Pt to SnO2 in the target powder is in the range of #imgabs0#. After the target powder is configured into an electrode slurry, an electrode layer is prepared by using the electrode slurry and adhered to both sides of a Nafion membrane to form a membrane electrode. Assembling the membrane electrode into the fuel cell type H2 gas sensor structure can greatly improve the sensor's detection sensitivity to hydrogen and reduce the sensor's detection limit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical gas sensors, and more specifically, relates to a fuel cell type H2 gas sensor, a membrane electrode and a preparation method thereof. Background Art

[0002] Hydrogen is colorless, odorless, low in density, and flammable. When its concentration exceeds 4%, it will explode. Therefore, many scenarios require accurate monitoring of hydrogen concentration. For example, in the metallurgical process, there is an important step of dry distillation, which is to remove impurities such as sulfur and nitrogen from coal, but a large amount of hydrogen will be released during the dry distillation process, which will cause safety hazards. Hydrogen will be produced during welding and electroplating. Due to its strong diffusion ability, hydrogen can easily penetrate into steel to form hydrogen embrittlement, and hydrogen embrittlement is irreversible, which seriously affects the service life of steel. Therefore, it is necessary to detect the hydrogen concentration. In the field of new energy vehicles, both hydrogen refueling stations and new energy vehicles themselves need to strictly monitor the hydrogen concentration to prevent hydrogen leakage and explosion. Therefore, it is increasingly important to develop a hydrogen sensor with good selectivity and low detection limit in production and life.

[0003] Currently, hydrogen gas sensors on the market are mainly divided into semiconductor, catalytic, electrochemical, etc. Among them, semiconductor type has the widest application and research scope, but the biggest problem of semiconductor type sensors is high power consumption, high operating temperature, and poor selectivity. Fuel cell type gas sensor belongs to electrochemical sensor, which overcomes the shortcomings of semiconductor gas sensor. It does not require external voltage, has low power consumption, can work at room temperature, and is green, environmentally friendly and pollution-free.

[0004] Traditional sensitive electrode materials are mostly based on carbon materials as carriers and Pt-modified catalysts. Due to the weak binding force between Pt and carbon, platinum particles are easily detached from the carbon carrier and agglomerated after long-term operation, resulting in a reduction in active sites, a decrease in response value, a shortened lifespan, poor long-term stability, and low detection sensitivity. Summary of the invention

[0005] In view of the above defects or improvement needs of the prior art, the present invention provides a fuel cell type H2 gas sensor, a membrane electrode and a preparation method thereof, the purpose of which is to improve the detection sensitivity of the fuel cell type gas sensor to hydrogen.

[0006] To achieve the above object, according to one aspect of the present invention, a method for preparing a membrane electrode for a fuel cell type H2 gas sensor is provided, comprising:

[0007] Add SnO2 powder or SnO2-Pd powder to chloroplatinic acid solution and add sodium citrate and stir to obtain substance A, wherein SnO2-Pd is SnO2 modified by Pd nanoparticles and SnO2 is nanospheres;

[0008] Add NaBH4 to NaOH solution to obtain sodium borohydride alkaline solution. Add sodium borohydride alkaline solution to substance A under ice-water bath conditions, and heat in a water bath at 60℃~90℃ for 1~2h to obtain substance B;

[0009] The substance B is centrifuged, washed, and dried to obtain a target powder, wherein the target powder is a Pt / SnO2 powder or a Pt / SnO2-Pd powder, wherein Pt / SnO2 is SnO2 modified by Pt nanoparticles, and Pt / SnO2-Pd is SnO2-Pd modified by Pt nanoparticles. The mass ratio of Pt:SnO2 in the target powder is in the range of

[0010] After the target powder is configured into electrode slurry, the electrode slurry is used to prepare the electrode layer and adhere it to both sides of the Nafion membrane to form a membrane electrode.

[0011] In one of the embodiments, the target powder is Pt / SnO2-Pd powder, wherein the mass percentage of Pd in ​​Pt / SnO2-Pd is in the range of [0.05% to 3%].

[0012] In one of the embodiments, the mass ratio of SnO2 or SnO2-Pd to chloroplatinic acid is (0.5:1) to (2:1), and the mass of sodium citrate is 0.5 to 1 times the mass of SnO2.

[0013] In one embodiment, the preparation process of SnO2-Pd powder includes:

[0014] SnO2 powder is dispersed in an aqueous solution and then dichlorotetraamminepalladium is added. After stirring, centrifugation, washing and drying, a sample powder is obtained. The sample powder is annealed at a high temperature in a muffle furnace to obtain SnO2-Pd powder.

[0015] In one embodiment, the pH of the sodium borohydride alkaline solution is ≥13.

[0016] In one embodiment, the target powder is configured into an electrode slurry, comprising:

[0017] Ethanol, 5 wt.% Nafion solution and deionized water are prepared into a dispersant in a volume ratio of (1-5): (1-3): (2-10);

[0018] The target powder is added to the dispersant and mixed evenly to obtain the electrode slurry.

[0019] In one embodiment, an electrode layer is prepared by using an electrode slurry and adhered to both sides of a Nafion membrane to form a membrane electrode, comprising:

[0020] The electrode slurry is dripped onto the surface of the polymer film and evenly coated, and then taken out after drying to obtain a polymer film with an electrode layer;

[0021] The polymer film with the electrode layer is hot pressed on both sides of the Nafion membrane at a temperature of 80-100°C and a pressure of 2-10 MPa and maintained for 60-120 seconds, and then the polymer film is peeled off to make the electrode layer adhere to both sides of the Nafion membrane to obtain a membrane electrode.

[0022] In one embodiment, before using the Nafion membrane, the Nafion membrane is further treated, and the treatment process includes: placing the Nafion membrane in a 5wt.% H2O2 solution, deionized water, 0.5mol / L~1mol / LH2SO4 solution, and deionized water at 70~90°C for 0.5~5h respectively, and the treated Nafion membrane is placed in deionized water for storage.

[0023] According to another aspect of the present invention, a membrane electrode for a fuel cell type H2 gas sensor is provided, comprising a Nafion membrane and electrode layers adhered to both sides of the Nafion membrane, wherein one electrode layer is a sensitive electrode and the other electrode layer is a counter electrode, the electrode layer comprises Pt / SnO2 or Pt / SnO2-Pd, wherein SnO2 is a nanosphere, Pt / SnO2 is SnO2 modified by Pt nanoparticles, Pt / SnO2-Pd is SnO2-Pd modified by Pt nanoparticles, SnO2-Pd is SnO2 modified by Pd nanoparticles, and the mass ratio of Pt:SnO2 in the electrode layer is in the range of

[0024] According to another aspect of the present invention, a fuel cell type H2 gas sensor structure is provided, including an upper cover, a gas chamber bracket, a sensitive electrode current collecting layer, a membrane electrode, a counter electrode current collecting layer, and a sensor back cover. The membrane electrode is the above-mentioned membrane electrode used in the fuel cell type H2 gas sensor.

[0025] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects compared with the prior art:

[0026] First, the electrode layer material of the membrane electrode prepared by the fuel cell type H2 gas sensor in the present application is different from the conventional electrode layer material. The conventional electrode layer material uses carbon material as a carrier, while the electrode layer material in the present application uses SnO2 as a carrier and is modified to make it suitable for fuel cell type H2 gas sensors. In the present application, SnO2 can be directly modified with Pt nanoparticles to obtain Pt / SnO2 as an electrode material; or SnO2 can be first modified with Pd nanoparticles to obtain SnO2-Pd, and then SnO2-Pd can be modified with Pt nanoparticles to obtain Pt / SnO2-Pd as an electrode material. At the same time, in order to make the fuel cell type H2 gas sensor have good detection sensitivity, the present application strictly controls the amount of Pt nanoparticles used so that the mass ratio of Pt:SnO2 is in range. At present, there has been no practice of using Pt / SnO2 or Pt / SnO2-Pd as sensitive electrodes in electrochemical sensors. SnO2 is a semiconductor material with poor conductivity. If it is directly used as a sensitive electrode in an electrochemical sensor, the electrochemical sensor will have difficulty in working properly. However, the inventors have found that by controlling the morphology of the SnO2 carrier, selecting suitable modification materials and controlling the mass ratio, the material can be used as a sensitive electrode, and the fuel cell type H2 gas sensor can achieve good detection effects. In this application, SnO2 in the form of nanospheres is used as a carrier, and Pt / SnO2 is obtained by modification with precious metals, or Pt / SnO2-Pd is obtained by modification with a small amount of Pd, and at the same time, the mass ratio of Pt:SnO2 is strictly controlled to be within . The preparation of sensitive electrodes can make the fuel cell type H2 gas sensor have good detection sensitivity, and subsequent experimental data also verified that the hydrogen sensor with Pt / SnO-Pd as the sensitive electrode material has a detection limit of hydrogen as low as 5ppm, and the hydrogen sensor with Pt / SnO2-Pd as the sensitive electrode material has a detection limit of hydrogen as low as 1ppm, which is much lower than the current electrochemical sensor detection limit of hydrogen.

[0027] Secondly, the present application also designs a membrane electrode preparation method for a fuel cell type H2 gas sensor, which is used to prepare the above-mentioned membrane electrode. In the preparation method, SnO2 powder or SnO2-Pd powder, chloroplatinic acid, and sodium borohydride are mixed together, and the reduced Pt nanoparticles are directly modified on the SnO2 or SnO2-Pd microspheres while the chloroplatinic acid and sodium borohydride undergo a reduction reaction. At the same time, sodium citrate is also added to the mixed solution to help the Pt nanoparticles be evenly coated on the SnO2 or SnO2-Pd microspheres, and finally a membrane electrode with good performance is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A schematic diagram of the structure of a fuel cell type hydrogen sensor according to an embodiment;

[0029] Figure 2 A flowchart of a method for preparing a membrane electrode for a fuel cell type H2 gas sensor according to an embodiment;

[0030] FIG3( a ) is a SEM image of a Pt / SnO2 electrode material according to an embodiment;

[0031] FIG3( b ) is a SEM image of a Pt / SnO2-Pd electrode material according to an embodiment;

[0032] Figure 4 The XRD diagram of Pt / SnO2 and Pt / SnO2-Pd electrode materials in one embodiment;

[0033] Figure 5 The response recovery curve of a fuel cell type H2 gas sensor using a Pt / SnO2 electrode to hydrogen gas according to an embodiment of the present invention is shown;

[0034] Figure 6 FIG. 1 is a response recovery curve of a fuel cell type H2 gas sensor using a Pt / SnO2-Pd electrode to low concentration hydrogen according to an embodiment of the present invention. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0036] First, the fuel cell type H2 gas sensor in this application is introduced. Figure 1 The figure shows a schematic diagram of the structure of a fuel cell type hydrogen sensor in an embodiment, which mainly includes an upper cover 1, an air chamber bracket 5, a sensitive electrode current collecting layer 6, a sensitive electrode 7, a Nafion membrane 8, a counter electrode 9, a counter electrode current collecting layer 10, a water vapor hole 11, a sensor back cover 12, and a water storage tank 13. Among them, the sensitive electrode 7, the Nafion membrane 8, and the counter electrode 9 form a membrane electrode. The sensor upper cover is provided with an electrode hole 2, a fixing hole 3, and a gas diffusion hole 4, and a waterproof and dustproof film is applied to the gas diffusion hole 4 to achieve hydrophobic dustproof. An activated carbon filter layer can be added in the middle of the gas diffusion chamber formed by the sensor upper cover 1 and the air chamber bracket 5, and the current collecting layer is connected to the electrode pin through the platinum wire passing through the electrode hole 2. Finally, the upper cover 1 is tightly packaged with the membrane electrode group and the back shell 12 by installing screws in the fixing hole 3, and the gap is filled with hot melt adhesive.

[0037] The current collecting layer is a stainless steel mesh. The size of the upper cover and the rear shell of the sensor is 2 to 3 cm. The radius of the diffusion hole is 0.5 mm to 1 mm. Put wet cotton with a solvent of 40% to 50% in the water storage tank, and the Nafion membrane can be moisturized through the water pores 11. At the same time, the remaining volume also ensures the existence of air to prevent the electrode from stopping the reaction due to the lack of oxygen.

[0038] The principle of fuel cell type H2 gas sensor is:

[0039] Sensitive electrode: H2-2e - =2H + ; (1)

[0040] Counter electrode: 1 / 2O2+2e - +2H + =H2O; (2)

[0041] When hydrogen enters the gas chamber through the gas diffusion hole and contacts the sensitive electrode, an oxidation reaction occurs and electrons are released. The electrons are conducted to the counter electrode current collecting layer through the sensitive electrode current collecting layer and the external circuit, and oxygen undergoes a reduction reaction at the counter electrode. The hydrogen ions generated by the sensitive electrode reaction are transmitted to the counter electrode through the Nafion membrane, forming an internal circuit. The concentration of hydrogen can be measured through the conversion relationship between current and concentration.

[0042] Therefore, in the fuel cell type H2 gas sensor, the role of the electrode is very critical, and it is a key factor affecting the detection sensitivity of the fuel cell type H2 gas sensor.

[0043] In the present application, the membrane electrode used includes a Nafion membrane and electrode layers adhered to both sides of the Nafion membrane, wherein one electrode layer is a sensitive electrode, and the other electrode layer is a counter electrode, and the electrode layer includes Pt / SnO2 or Pt / SnO2-Pd, wherein SnO2 is a nanosphere, Pt / SnO2 is SnO2 modified by Pt nanoparticles, Pt / SnO2-Pd is SnO2-Pd modified by Pt nanoparticles, SnO2-Pd is SnO2 modified by Pd nanoparticles, and the mass ratio of Pt:SnO2 in the electrode layer is in the range of Specifically, the mass ratio of Pt:SnO2 can be Furthermore, the mass ratio of Pt:SnO2 in the electrode layer is preferably In one embodiment, when the electrode layer includes Pt / SnO2-Pd, in addition to controlling the mass proportion of Pt nanoparticles, the mass proportion of Pd nanoparticles can also be adjusted to optimize device performance. Specifically, the mass proportion of Pd in ​​Pt / SnO2-Pd is in the range of [0.05% to 3%]. Compared with Pt / SnO2, a small amount of Pd is added to obtain Pt / SnO2-Pd, which can further improve the device's detection limit for hydrogen.

[0044] The following is a method for preparing a membrane electrode for use in a fuel cell type H2 gas sensor. Figure 2 As shown, the preparation method comprises:

[0045] Step S100: Add SnO2 powder or SnO2-Pd powder to chloroplatinic acid solution and add sodium citrate and stir evenly to obtain substance A, wherein SnO2-Pd is SnO2 modified by Pd nanoparticles, and SnO2 is nanospheres.

[0046] Prior to this, SnO2 powder needs to be prepared, and SnO2 is nanosphere particles. In one embodiment, tin tetrachloride, anhydrous ethanol, and deionized water can be mixed in a certain proportion, stirred evenly, and then a 35-40wt% hydrochloric acid solution is added, and the stirring is continued to be evenly, and the obtained dispersion is placed in a reactor, reacted at 180-220°C for 10-36h, and then solid-liquid separation and washing are performed to obtain tin oxide hollow nanosphere particles.

[0047] When the added powder is SnO2-Pd powder, SnO2-Pd powder needs to be prepared in advance, where SnO2-Pd is SnO2 modified with Pd nanoparticles. In one embodiment, SnO2-Pd powder is prepared by the following method:

[0048] SnO2 powder is dispersed in deionized water, and dichlorotetraammine palladium and 100-300 ml deionized water are added, stirred at room temperature for 12-72 hours, centrifuged and washed, and dried at 50-80°C; the dried sample is placed in a muffle furnace and annealed at 500-900°C for 2-6 hours to obtain SnO2-Pd powder, wherein Pd is attached to the surface of SnO2 particles. In one embodiment, the mass ratio of dichlorotetraammine palladium to SnO2 is (0.001-0.02):1.

[0049] After obtaining SnO2 powder or SnO2-Pd powder, add SnO2 powder or SnO2-Pd powder to chloroplatinic acid H2PtCl6 solution, stir for 8 to 12 minutes, add sodium citrate, continue stirring for 25 to 35 minutes, mix evenly, and obtain substance A, in which SnO2 powder or SnO2-Pd powder is evenly dispersed in substance A. In one embodiment, the mass ratio of SnO2 or SnO2-Pd to chloroplatinic acid is (0.5:1) to (2:1), and the mass of sodium citrate is 0.5 to 1 times the mass of SnO2

[0050] Step S200: Add NaBH4 to NaOH solution to obtain sodium borohydride alkaline solution, add the sodium borohydride alkaline solution to substance A under ice-water bath conditions, heat in a water bath at 60°C to 90°C for 1 to 2 hours, and react to obtain substance B.

[0051] A certain amount of NaOH is dissolved in deionized water to obtain an alkaline solution, and then sodium borohydride NaBH4 is added to obtain a sodium borohydride alkaline solution. Specifically, the pH of the sodium borohydride alkaline solution is ≥ 13. In one embodiment, in 50 ml of deionized water, the mass of sodium borohydride is 0.02-0.08 g, and the mass of NaOH is 0.1-0.4 g.

[0052] In an ice-water bath, use a pipette to dropwise add sodium borohydride alkaline aqueous solution into substance A, and ultrasonicate for 10 to 30 minutes. At this time, sodium borohydride NaBH4 and chloroplatinic acid H2PtCl6 mainly react as follows:

[0053] 2PtCl6 2- +BH 4- +4H2O=2Pt+B(OH) 4- +8H + +12Cl - ;

[0054] While reducing Pt, Pt nanoparticles are modified on the surface of SnO2 or SnO2-Pd. At the same time, due to the addition of sodium citrate, the Pt nanoparticles can be evenly and stably distributed on the surface of SnO2 or SnO2-Pd.

[0055] After the dropwise addition is completed, heat in a water bath at 60°C to 90°C for 1 to 2 hours to obtain substance B.

[0056] Step S300: Centrifuge and wash the substance B, and then dry it to obtain the target powder, which is Pt / SnO2 powder or Pt / SnO2-Pd powder, wherein Pt / SnO2 is SnO2 modified by Pt nanoparticles, and Pt / SnO2-Pd is SnO2-Pd modified by Pt nanoparticles. The mass ratio of Pt:SnO2 in the target powder is in the range of

[0057] Specifically, substance B was washed three times by centrifugation with ethanol and deionized water, respectively, and dried at 60-70° C. for 10-14 hours to obtain the target powder.

[0058] Step S400: After the target powder is configured into an electrode slurry, the electrode slurry is used to prepare an electrode layer and adhere it to both sides of the Nafion membrane to form a membrane electrode.

[0059] Before preparing the membrane electrode, a Nafion membrane needs to be prepared for use. In one embodiment, the treatment process of the Nafion membrane includes: placing the Nafion membrane in a 5wt.% H2O2 solution, deionized water, 0.5mol / L-1mol / L H2SO4 solution, and deionized water at 70-90°C for 0.5-1.5 hours respectively, and placing the cleaned Nafion membrane in deionized water for storage.

[0060] After obtaining the target powder, prepare the membrane electrode:

[0061] Prepare a dispersant by mixing ethanol, 5wt.% Nafion solution and deionized water in a volume ratio of (1-5): (1-3): (2-10). Add the target powder to the dispersant and mix well to obtain an electrode slurry. Use a pipette to drip onto an area of ​​0.5cm fixed with tape. 2 ~5cm 2 The PTFE membrane surface is coated evenly with a scraper, dried at 65°C, taken out, and the tape is removed to obtain a PTFE membrane with an electrode layer having a fixed shape.

[0062] Two PTFE membranes with electrode layers are hot pressed on both sides of a Nafion membrane at 80-100°C, 2-10 MPa, and 60-120s, and the PTFE membranes are peeled off to obtain a membrane electrode.

[0063] Through the above method, a membrane electrode that can be used in a fuel cell type H2 gas sensor can be prepared. By assembling the membrane electrode into a fuel cell type H2 gas sensor, the sensor's detection sensitivity to hydrogen can be improved.

[0064] Two specific embodiments are described below.

[0065] Example 1

[0066] 1. Preparation of Pt / SnO2 electrode materials:

[0067] (1) Take 10 mg of SnO2 powder, add 10.5 ml of 50 mmol H2PtCl6 solution, stir for 10 min, add 0.3 mg of trisodium citrate, stir for 30 min, and obtain substance A;

[0068] (2) Take 0.2 g of NaOH, add 50 ml of deionized water to dissolve, then add 0.05 g of NaBH4, test pH = 13, and obtain an alkaline aqueous solution of sodium borohydride;

[0069] (3) In an ice water bath, add sodium borohydride alkaline aqueous solution dropwise into substance A using a pipette. After the addition is complete, stir in an 80° C. water bath for 2 hours to obtain substance B;

[0070] (4) Substance B was taken and washed three times by centrifugation with ethanol and deionized water respectively, and dried at 65°C for 12 hours to obtain a Pt / SnO2 electrode material. Its SEM image is shown in FIG3(a). The modified Pt / SnO2 is nano-spherical as a whole, and its XRD curve is shown in FIG3(b). Figure 4 shown.

[0071] 2. Membrane electrode preparation:

[0072] Take 10 mg of Pt / SnO2 powder and ultrasonically mix it with 100 μL of a dispersant composed of ethanol, 5 wt.% Nafion solution, and deionized water in a volume ratio of 2:1:4 for 30 minutes to obtain an electrode slurry. Use a pipette to add it dropwise to the surface of a PTFE membrane of a size of 1 cm*1 cm fixed with tape, and use a scraper to evenly coat it. After drying at 65°C, take it out and remove the tape to obtain a PTFE membrane with a sensitive electrode material of a fixed shape. Repeat twice, hot-press two PTFE membranes with sensitive materials on both sides of the Nafion membrane at 90°C, 8 MPa, and 90s, peel off the PTFE membrane, and you can get a membrane electrode.

[0073] 3. Assemble the above membrane electrode into a fuel cell type H2 gas sensor.

[0074] After testing, the response recovery curve of the above fuel cell type H2 gas sensor to hydrogen is as follows: Figure 5 As shown, it can be seen that using the Pt / SnO2 sensitive electrode, the detection limit can be as low as 5ppm.

[0075] Example 2

[0076] 1. Preparation of Pt / SnO2-Pd electrode material:

[0077] (1) 300 mg SnO2 and 1.12 mg dichlorotetraamminepalladium monohydrate were added to 200 ml deionized water, stirred at room temperature for 48 hours, centrifuged and washed, and dried at 65°C; the dried sample was annealed in a muffle furnace at 800°C for 5 hours to obtain SnO2-Pd powder;

[0078] (2) Take 10 mg of SnO2-Pd powder, add 10.5 ml of 50 mmol H2PtCl6 solution, stir for 10 min, add 0.3 mg of trisodium citrate, stir for 30 min, and obtain substance A;

[0079] (3) Take 0.2 g of NaOH, add 50 ml of deionized water to dissolve, then add 0.05 g of NaBH4, test pH = 13, and obtain an alkaline aqueous solution of sodium borohydride;

[0080] (4) In an ice water bath, add sodium borohydride alkaline aqueous solution dropwise into substance A using a pipette. After the addition is complete, stir in an 80° C. water bath for 2 hours to obtain substance B;

[0081] (5) Substance B was taken and washed three times by centrifugation with ethanol and deionized water respectively, and dried at 65°C for 12 hours to obtain a Pt / SnO2-Pd electrode material. Its SEM image is shown in FIG3(b). The modified Pt / SnO2-Pd is nano-spherical as a whole and its XRD curve is shown in FIG3(c). Figure 4 shown.

[0082] 2. Membrane electrode preparation:

[0083] The Pt / SnO2 powder in Example 1 was replaced with Pt / SnO2-Pd powder, and the other steps were the same as in Example 1 to prepare a membrane electrode.

[0084] 3. Assemble the above membrane electrode into a fuel cell type H2 gas sensor.

[0085] After testing, the response recovery curve of the above fuel cell type H2 gas sensor to hydrogen is as follows: Figure 6 As shown, it can be seen that using the Pt / SnO2-Pd sensitive electrode, the detection limit can be as low as 1ppm. The effect of the Pt / SnO2-Pd sensitive electrode is better than that of the Pt / SnO2 sensitive electrode, and is much lower than the current fuel cell type sensor's detection limit for hydrogen.

[0086] In summary, the present invention uses SnO2 in the form of nanospheres as a carrier and obtains Pt / SnO2 or Pt / SnO2-Pd by modification with noble metals, while strictly controlling the mass ratio of Pt:SnO2 to be within In the range of , the Pd mass fraction is 0.05% to 3%. The preparation of sensitive electrodes in this way can make the fuel cell type H2 gas sensor have good detection sensitivity. Subsequent experimental data also verified that its hydrogen detection limit is as low as 1ppm, which is much lower than the current electrochemical sensor detection limit for hydrogen, and has good application prospects.

[0087] It will be easily understood by those skilled in the art that the above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a membrane electrode for a fuel cell type H2 gas sensor, characterized in that: include: Add SnO2-Pd powder to chloroplatinic acid solution and add sodium citrate and stir to obtain substance A, wherein the mass ratio of SnO2-Pd to chloroplatinic acid is (0.5:1) to (2:1), the mass of sodium citrate is 0.5 to 1 times the mass of SnO2, wherein SnO2-Pd is SnO2 modified by Pd nanoparticles, and SnO2 is hollow nanospheres; Add NaBH4 to NaOH solution to obtain sodium borohydride alkaline solution, the pH of the sodium borohydride alkaline solution is ≥ 13, add the sodium borohydride alkaline solution to substance A under ice water bath conditions, and heat in a water bath at 60℃~90℃ for 1~2h to obtain substance B; The material B is centrifuged, washed, and dried to obtain the target powder, wherein the target powder is Pt / SnO2-Pd powder, wherein Pt / SnO2-Pd is SnO2-Pd modified with Pt nanoparticles, and the mass ratio of Pt:SnO2 in the target powder is in the range of , the mass proportion of Pd in ​​Pt / SnO2-Pd is in the range of [0.05%~3%]; After the target powder is configured into an electrode slurry, the electrode slurry is used to prepare an electrode layer and adhered to both sides of the Nafion membrane to form a membrane electrode, wherein the mass ratio of Pt:SnO2 in the electrode layer is in the range of .

2. The membrane electrode preparation method according to claim 1, characterized in that: The preparation process of SnO2-Pd powder includes: SnO2 powder is dispersed in an aqueous solution and then dichlorotetraamminepalladium is added. After stirring, centrifugation, washing and drying, a sample powder is obtained. The sample powder is annealed at a high temperature in a muffle furnace to obtain SnO2-Pd powder.

3. The membrane electrode preparation method according to claim 1, characterized in that: The target powder is formulated into an electrode slurry, including: Prepare a dispersant by mixing ethanol, 5wt.% Nafion solution and deionized water in a volume ratio of (1-5):(1-3):(2-10); The target powder is added to the dispersant and mixed evenly to obtain the electrode slurry.

4. The membrane electrode preparation method according to claim 1, characterized in that: The electrode layer is prepared by using electrode slurry and adhered to both sides of the Nafion membrane to form a membrane electrode, including: The electrode slurry is dripped onto the surface of the polymer film and evenly coated, and then taken out after drying to obtain a polymer film with an electrode layer; The polymer film with the electrode layer is hot pressed on both sides of the Nafion membrane at a temperature of 80-100°C and a pressure of 2-10 MPa and maintained for 60-120 seconds, and then the polymer film is peeled off to make the electrode layer adhere to both sides of the Nafion membrane to obtain a membrane electrode.

5. The membrane electrode preparation method according to claim 1, characterized in that: Before using the Nafion membrane, the Nafion membrane is also treated, and the treatment process includes: placing the Nafion membrane in a 5wt.% H2O2 solution, deionized water, 0.5mol / L~1mol / L H2SO4 solution, and deionized water at 70~90°C for 0.5~1.5 hours respectively, and the treated Nafion membrane is placed in deionized water for storage for later use.

6. A membrane electrode for a fuel cell type H2 gas sensor prepared by the method according to any one of claims 1 to 5, characterized in that: The invention comprises a Nafion membrane and electrode layers adhered to both sides of the Nafion membrane, wherein one electrode layer is a sensitive electrode and the other electrode layer is a counter electrode, wherein the electrode layer comprises Pt / SnO2-Pd, wherein SnO2 is a hollow nanosphere, Pt / SnO2-Pd is SnO2-Pd modified by Pt nanoparticles, SnO2-Pd is SnO2 modified by Pd nanoparticles, and the mass ratio of Pt:SnO2 in the electrode layer is in the range of The mass proportion of Pd in ​​Pt / SnO2-Pd is in the range of [0.05%~3%].

7. A fuel cell type H2 gas sensor structure, comprising an upper cover, a gas chamber bracket, a sensitive electrode current collecting layer, a membrane electrode, a counter electrode current collecting layer, and a sensor back cover, characterized in that: The membrane electrode is the membrane electrode for use in a fuel cell type H2 gas sensor as claimed in claim 6.

Citation Information

Patent Citations

  • Palladium monatomic modified tin oxide composite material as well as preparation method and application thereof

    CN112924498A

  • Electrochemical hydrogen sensor based on membrane electrode and application thereof

    CN113671008A

Cited By

  • Membrane electrode of gas sensor and preparation method and application thereof

    CN117110393A

  • Preparation method and application of catalyst and membrane electrode of fuel cell type sensor

    CN118204107A

  • A method for manufacturing a catalyst and a membrane electrode for a fuel cell type sensor and applications thereof

    CN118204107B